Respuesta :

Answer:

12

Step-by-step explanation:

All you have to is plug in the values. (Don't forget PEMDAS.)

Parentheses (Comes first)

Exponents

Multiplication

Division

Addition

Subtraction (Comes last)

x = 1

y = 1

6(1+1)

6(2)

= 12

Hope this helped! :)

Answer:

the answer is 12

Step-by-step explanation:

6(x+y)

x=1 and y=1

so what you do is that you replace x and y with 1

then since there's parenthesis you have to distruibute

6 time 1 equals 6 and 6 times 1 equals 6

so then you add 6+6= 12